An Improvement Intended For Multiple Crack Diagnosis Adopting Combo Artificial Intelligence Technique - Nanda, Jajneswar; Das, Layatitdev; R. Parhi, D (International Journal of Engineering and Technology, 2018)
Abstract: In the existing article, an innovative combination technique has been efficiently implemented to properly recognize the specific position and intensity of the transverse surface crack in a fixed-fixed shaft. The rod is suitably fixed on two modest bearings at both ends including axial and twisting load for the fixed angular arrangement in the longitudinal direction. The fluctuation parametric measure so as expected frequencies, mode shapes are interrogated in the  proximity of two crack depths (bi) with their specific locations (Li) using stress intensity factor. Stress intensity factor is typically an objective function of compliance matrices. It is estimated as implementing one desired end of the shaft as the fixed bearings with the considerable help of an analytical method. The identical shaft is designed precisely to accurately determine the vibration signatures at respective vicinity using correctly an experimental procedure.A developed methodology MANFIS-GA (an inverse technique) is implemented correctly to identify the proper position and intensity of possible crack from any one of the direct bearing. Complex MANFIS system consists precisely of four composed ANFIS layer. The possible input to every ANFIS step is adequately equipped with the first three fundamental frequencies along with their modal values. The standard output of the active ANFIS part prognosticates the interim crack positions and desired depths. The interim outputs from four ANFIS (MANFIS) are carefully taken as the specific inputs to the automated G.A. system. The outputs from the modern G.A. system are invariably final crack locations along with crack depths. The potency of the satisfactory MANFIS-GA results is authenticated by correlating the results with the experimental setup. By reasonably interpreting the possible outcomes, it is presumed that this recommended methodology is valid for online and time saving for fault analysis of the cracked structure.